Glutathione is a factor of resistance of Jurkat leukemia cells to nitric oxide‐mediated apoptosis - Umansky, Viktor; Dröge, Wulf (Journal of cellular biochemistry, 2000)
We have previously reported that nitric oxide (NO) stimulates apoptosis in different human neoplastic lymphoid cell lines through mitochondrial damage (including degradation of cardiolipin, a major mitochondrial lipid) followed by activation of caspases.
Gesehen am 03.02.2021